ANALISIS PERHITUNGAN ZAKAT PROFESI DALAM SATUAN BRUTO DAN NETTO MENURUT HUKUM ISLAM - St. Rahmawati (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2018)
Professional zakat is zakat issued from income, salary, services, wages or honorarium obtained by lawful means when it has arrived at the Nisab. The issuance of professional zakat is wiser and better if the community issues zakat from the total assets they get after the basic needs are met (net) in this case clothing, shelter, food, and basic necessities are no more than that. One fundamental mistake is to ignore the philosophy of Nisab and the occurrence of the determination of Nisab based on Gross (Gross) and Net (Net) income, which implies the uncertainty of professional zakat in addition to the practice of the syara order.